Synthesis and characterization of surface-functionalized paramagnetic nanoparticles and their application to immobilization of α-acetolactate decarboxylase. Issue 9 (September 2015) - Qian, Siriguleng; Wang, Chun; Wang, Hongying; Yu, Fang; Zhang, Chunzhi; Yu, Hongshan
Graphical abstract Schematic representation of synthesis of surface-functionalized PMN Fe3O4@SiO2NH2 NPs (a) and its application to α-ALDC immobilization (b).